Tracing COVID-19 Source of Infection Among Health Personnel in a Pediatric Hospital - Daniela de la Rosa-Zamboni; Fernando Ortega-Riosvelasco; Nadia González-García; Ana Estela Gamiño-Arroyo; Guillermo Alejandro Espinosa-González; Juan Manuel Valladares-Wagner; Araceli Saldívar-Flores; Olivia Aguilar-Guzmán; Juan Carlos Sanchez-Pujol; Briseida López-Martínez; Mónica Villa-Guillén; Israel Parra-Ortega; et al. (Frontiers Media S.A., 2022)
Health personnel (HP) have been universally recognized as especially susceptible to COVID-19. In Mexico, our home country, HP has one of the highest death rates from the disease. From the beginning of the SARS-CoV-2 pandemic, an office for initial attention for HP and a call center were established at a COVID-19 national reference pediatric hospital, aimed at early detection of COVID-19 cases and stopping local transmission. The detection and call center implementation and operation, and tracing methodology are described here. A total of 1,042 HP were evaluated, with 221 positive cases identified (7.7% of all HP currently working and 26% of the HP tested). Community contagion was most prevalent (46%), followed by other HP (27%), household (14%), and hospitalized patients (13%). Clusters and contact network analysis are discussed. This is one of the first reports that address the details of the implementation process of contact tracing in a pediatric hospital from the perspective of a hybrid hospital with COVID-19 and non-COVID-19 areas.